THE RELATIONSHIP BETWEEN RISK MANAGEMENT AND FIRM PERFORMANCE - EVIDENCE FROM THE GEORGIAN MANUFACTURING INDUSTRY - Vakhtang BERISHVILI; Sevinji MAMEDOVA (Financial Studies)
This paper investigates the existence of the relationship between risk management (RM) and the financial performance of Georgian manufacturing firms. By looking into risk management information disclosures of manufacturing companies in Georgia for the year 2021, seven factors were studied to assess the RM level they used. RM factors were chosen based on the Enterprise Risk Management (ERM) requirements of two leading risk management standards: ISO 31000:2018 and COSO (2017). The Risk Management Disclosure score (RMD) was designed and calculated. The study analysed performance measures of a firm represented by: Operating Profit Margin, Non-operating Profit Margin, Net Profit Margin, ROA and ROE. OLS regression was used to reveal the relationship between RMD and performance. The results show a positive linkage between RMD and Operating and Net Profit Margins. On the other hand, no linkage is found between RMD and other measures. The study highlights how effective risk management enhances firm performance, aiding managers and policymakers. From the theoretical aspect, the study contributes to the literature by reinforcing the link between risk management and firm performance and offering an updated framework for further empirical research using RMD.